A comparison of the shear bond strength of conventional acid etching, self-etching primer, and single bottle self-adhesive - An In vitro study - Aman Sachdeva; Shweta Raghav; Munish Goel; Namita Raghav; Sudhanshu Tiwari (Wolters Kluwer Medknow Publications, 2017)
Background: Bonding of brackets to enamel has been a critical issue in orthodontic research since the significance of achieving a stable bond between the tooth and its bracket was obvious from the onset. This study aimed to determine the shear bond strength (SBS) of self-adhesive system, to compare SBS of conventional etchant, self-etching prime and self-adhesive system under dry condition, and to estimate the chair-side time saved for the application of the bonding agents.